Equal Opportunities for Networked Learners - Howell, Barbara (Proceedings of the International Conference on Networked Learning, 2000)
Research has been conducted on the relationship between gender and dialogue content in computer mediated environments. This paper, however, focuses on establishing possible and plausible links between gender and Learning styles in a Networked Learning (NL) environment. The findings of a questionnaire distributed to M.Sc. Networked Information Engineering (NIE) students show some significant differences between male and female respondents. In particular, the results illustrating communication processes highlight interesting and perhaps unusual differences between. the genders. These findings may facilitate practitioners to focus on the relationship between. gender and the range of modalities available in the NL experience. Furthermore, 1he potential to promote equal learning opportunities.